The relationship between workload and job performance in private higher education institutions: a case study in Kolej Poly-Tech MARA, Northern Malaysia / Muhamad Nasrullah Zamri ... [et al.] - Zamri, Muhamad Nasrullah; Wan Ab. Aziz, Wan Asri; Rasak, Nor Tasnim Syahera; Suhaimi, Muhammad Hafiz (Universiti Teknologi MARA, Terengganu, 2024)
Workload is a significant issue impacting employee job performance. Heavy workloads often lead to decreased performance, which lowers morale and increases employee turnover within organizations. This study focused on workload as a job stressor and its effects on job performance. The aim was to explore the relationship between workload and job performance among employees at Kolej Poly-Tech MARA, Northern Malaysia. Quantitative data were gathered through questionnaires distributed to 127 employees of the institution. The analysis revealed a moderate negative and significant relationship between workload and job performance (r=-0.528, p<.05) at Kolej Poly-Tech MARA, Northern Malaysia. Consequently, workload directly affects job performance at this institution. Recommendations include improving the current information systems and procedures to eliminate redundant tasks, revising employee salaries and benefits, and, if funds permit, hiring additional employees to alleviate the workload on current employees. Future research should consider comparing public and private universities or colleges to assess differences in stress levels. Additionally, increasing the number of respondents and including other branches of Kolej Poly-Tech MARA could enhance the study. Finally, expanding the conceptual framework by incorporating more variables and applying different analytical methods, such as SEM-PLS, would further benefit future research.